The responses by gut-associated and bronchus-associated lymphoid tissues of buffalo calves following oral exposure to Pasteurella multocida B:2 - Abubakar, Muhammad Salisu; Saad, Mohd Zamri; Sabri, Jasni; Abu Bakar @ Zakaria, Md Zuki (Universiti Putra Malaysia Press, 2014)
This report describes the mucosal immune response in the gastro-intestinal and respiratory tracts of buffalo calves following oral exposure to live wild-type Pasteurella multocida B:2. Nine buffalo calves of approximately 8 months old were treated with intramuscular injections of dexamethasone for 3 consecutive days before they were divided into 3 groups. Calves of group 1 were exposed orally to 50 ml inoculums containing 109 colony forming units (CFU)/ml of live wild-type P. multocida B:2. Calves of group 2 were exposed intratrachea with 5ml of the same inocula while calves of group 3 were given 50ml of PBS orally. At the end of day 7 post-exposure, all surviving calves were killed and organs of gastrointestinal and respiratory tracts were processed for histology examination. The presence of lymphoid nodules, the size of the nodules and the number of lymphocytes were noted. Both oral and intra-trachea exposures elicited mucosal responses in both gastro-intestinal and respiratory tracts. Oral exposure stimulated significantly (p <0.05) superior mucosalresponse in the gastrointestinal tract, while intratracheal exposure stimulated significantly (p<0.05) superior mucosal response in the respiratory tract. Overall, oral exposure was ableto stimulate the distance mucosal sites such as the respiratory tract and provides potential use for oral administration of live vaccine against haemorrhagic septicaemia.